You should solve the improper integral `int_3^oo f'(x)e^(-x/6)dx` , using integration by parts such that:

`int udv = uv - int vdu`

You should consider `u = f(x) => du = f'(x)dx ` and `dv= e^(-x/6)dx => v = int e^(-x/6)dx` Using the substitution `-x/6 = t => -dx/6 = dt => dx = -6dt ` yields:

`int e^t*(-6dt) = -6e^t + c => v = -6e^(-x/6)`

Hence, evaluating the integral yields:

`int_3^n f(x)e^(-x/6)dx = -6f(x)e^(-x/6)+ 6int_3^n f'(x)*e^(-x/6)dx`

Since the problem provides the information that `lim_(n->oo)int_3^n f(x)e^(-x/6)dx = -8` , hence, you may evaluate `int_3^n f'(x)*e^(-x/6)dx` such that:

`-8 = lim_(n->oo)(-6f(n)e^(-n/6)+...

(The entire section contains 407 words.)

## Unlock This Answer Now

Start your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Posted on